The Lung Health Study - J Manfreda; NR Anthonisen; The Lung Health Study Research Group (Canadian Respiratory Journal)
OBJECTIVE: To determine whether smoking intervention and use of an inhaled bronchodilator can slow the rate of decline in forced expiratory volume in 1 s (FEV1) in smokers with mild obstructive pulmonary disease.